Hidden competence: women's mathematical participation in public and private classroom spaces - Ernest, Jessica Brooke; Reinholz, Daniel L.; Shah, Niral (Educational studies in mathematics, 2019)
This paper reports on gender and participation in one inquiry-oriented undergraduate mathematics course. While there is evidence that inquiry can better support all learners, especially women, less is known about the distribution of participation in inquiry classrooms. Here, we focus on how men and women participated in both public spaces (in plenary with the whole class) and private spaces (with their group members). We found that while many women provided a large number of high-level "why" contributions in their groups, this did not necessary translate to participation in plenary discussions. We thus argue that women's competence was hidden to the whole class, which contributes to the systematic marginalization of women in mathematics.